Economia criativa: acesso e distribuição de bens culturais - Carvalho, Leandro de (2009)
Creative economy is the theme that permeates the discussion of this work. While discussing its definitions, its scope and its size, the attention was focused on two of its aspects: access and distribution of cultural goods. These aspects were chosen based on the tension that was noticed in the cultural production: on the one hand, the music and audiovisual industry with a business model that makes profit, creating scarcity through the medium (physical environment), being controled and restrict; on the other hand, the movement of technology users, especially Internet users, promoting actions that undermine the bases of cultural industry: they make the support desnecessary and the access becomes unrestricted and fast, and change the ways of distribution, through the channels of sharing and viewing of any cultural production, that can be seen using the nearest computer. In light of these events and tensions, the development of the computer is discussed in this research: from the machine for storage only, to the machine of access. It´s also discussed, at this study, the global network as the great diffuser of cultural production, especially for small producers. Finally, it was concluded that the creation of new production facilities for cultural, musical and audiovisual areas reveal an important contradiction: the environments of greatest enhancement of access, innovation, creativity and culture (based on analysis of Rifkin), could be completely appropriated by the cultural industry, taking up the changes in perceptions of the demands. However, alongside this new type of incentive, the global network provides tools in order to completely unlink creation, distribution and access, minimizing any attempt of the cultural industry in the sense of total control of what is produced and distributed as a cultural good. New possibilities for the culture producer were placed and this professional can select and, possibly, depend less on the big cultural industry in order to feed their lives, through their art